واقع اقتصاد المعرفة في الجامعات اليمنية من وجهة نظر أعضاء هيئة التدريس: دراية ميداتية في جامعتي صنعاء والعلوم والتكتولوجيا اليمنية = The current situation of knowledge economy at Yemeni Universities from academic staff perspectives: a field study at Sana'a University and University of Science and Technology - Al-Azizi, Mahmood Abdo Hasan; Al-Hidabi, Dawood Abdulmalek Yahya (University of Science and Technology, Yemen, 2017)
The purpose of the research was to assess the current situation of the knowledge economy in the Yemeni universities (Public and private) from the point of view of their faculty members. A further investigation into the possible significant differences between faculty members’ views regarding the knowledge economy in both Yemeni public and private universities was also attempted. In order to achieve the objectives of the research, the researchers used the descriptive approach, and designed a questionnaire as the research tool which consisted of four main dimensions: research, development, innovation, education and training, ICT infrastructure, and governance. The validity and reliability of the tool were statistically checked, and data was analyzed using SPSS program. The study revealed the following results: